Poems, new and collected, 1957-1997 - Szymborska, Wistawa frey50; Baranczak, Stanisaw 1946-; Cavanagh, Clare (New York Harcourt, Inc, 2000)
Here is the definitive collection of Wislawa Szymborska's poetry in English. It includes the one hundred poems of her phenomenally popular View with a Grain of Sand, along with sixty-four additional poems newly translated for this volume. Szymborska's Nobel Prize acceptance address is also included.
The poet and the world (Nobel Lecture) -- from Calling out to yeti 1957: I'm working on the world ; Classifieds ; Greeting the supersonics ; An effort ; Four A.M. ; Still life with a balloon ; To my friends ; Funeral (I) ; Brueghel's two monkeys ; Still ; Atlantis ; Notes from a nonexistent Himalayan expedition ; Nothing twice ; Buffo ; Commemoration -- from Salt 1962: The monkey ; Lesson ; Museum ; A moment in Troy ; Shadow ; The rest ; Clochard ; Vocabulary ; Travel elegy ; Without a title ; An unexpected meeting ; Golden anniversary ; Starvation camp near Jaslo ; Parable ; Ballad ; Over wine ; Rubens' women ; Coloratura ; Bodybuilders' contest ; Poetry reading ; Epitaph ; Prologue to a comedy ; Likeness ; I am too close ... ; The Tower of Babel ; Water ; Synopsis ; In Heraclitus's river ; Conversation with a stone -- No end of fun 1967 -- from Could have 1972 -- from A large number 1976 -- The people on the bridge 1986 -- The end and the beginning 1993 -- New Poems 1993-97 -- Index of forst lines..
"A Harvest Book"
Keywords: Szymborska, Wisawa